Face masks as floating signifiers during the COVID-19 pandemic in Belgium. Issue 2 (15th March 2021) - Van Gorp, Baldwin
Abstract : Research-based drawings are used to demonstrate how face masks functioned as floating signifiers in the public space in Belgium during the 2020 pandemic. Face masks have become the external hallmark of a pandemic caused by SARS-CoV-2, a potentially life-threatening virus that is, by definition, invisible. Paradoxically, the presence of face masks seems to indicate a risk of infection, while the absence of face masks indicates safety. Unlike in Asian countries, a mask is not a sign of solidarity in Belgium; it is a personal attribute that can be worn in many different ways. These observations are contrasted with how medical personnel is wearing protective equipment in a COVID-19 unit at a hospital.